Peningkatan Hasil Belajar Peserta Didik Melalui Culturally Responsive Teaching Berbantuan Media Interaktif - Wiri, Paul Erikson Wada; Tokan, Moses Kopong (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2025)
This study is a classroom action research that describes the application of the CRT approach combined with the PBL model in improving the quality of learning and mathematics learning outcomes, conducted in two cycles with one meeting per cycle. Data were obtained through observation sheets and learning outcome tests. Subsequently, it was analyzed descriptively qualitative and quantitative. The results of the research obtained there is an increase: 1) student learning outcomes from pre-cycle to cycle I and cycle I to cycle II, respectively by 36.66% and 26.27%; 2) teacher activity by 2.6% from cycle I to cycle II, and 3) student activity by 6.2% from cycle I to cycle II. These results indicate that the use of the CRT approach combined with the PBL model improves learning outcomes, and teacher and student activities through the use of effective interactive media.